Corticosteroids for acute bacterial meningitis - Brouwer, Matthijs C; McIntyre, Peter; de Gans, Jan; Prasad, Kameshwar; van de Beek, Diederik (Cochrane database of systematic reviews, 2010)
In experimental studies, the outcome of bacterial meningitis has been related to the severity of inflammation in the subarachnoid space. Corticosteroids reduce this inflammatory response. To examine the effect of adjuvant corticosteroid therapy versus placebo on mortality, hearing loss and neurological sequelae in people of all ages with acute bacterial meningitis. We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2010, issue 1), MEDLINE (1966 to February 2010), EMBASE (1974 to February 2010) and Current Contents (2001 to February 2010). Randomised controlled trials (RCTs) of corticosteroids for acute bacterial meningitis. We scored RCTs for methodological quality. We collected outcomes and adverse effects. We performed subgroup analyses for children and adults, causative organisms, low-income versus high-income countries, time of steroid administration and study quality. Twenty-four studies involving 4041 participants were included. Similar numbers of participants died in the corticosteroid and placebo groups (18.0% versus 20.0%; risk ratio (RR) 0.92, 95% confidence interval (CI) 0.82 to 1.04, P = 0.18). There was a trend towards lower mortality in adults receiving corticosteroids (RR 0.74, 95% CI 0.53 to 1.05, P = 0.09). Corticosteroids were associated with lower rates of severe hearing loss (RR 0.67, 95% CI 0.51 to 0.88), any hearing loss (RR 0.76, 95% CI 0.64 to 0.89) and neurological sequelae (RR 0.83, 95% CI 0.69 to 1.00).Subgroup analyses for causative organisms showed that corticosteroids reduced severe hearing loss in Haemophilus influenzae meningitis (RR 0.34, 95% CI 0.20 to 0.59) and reduced mortality in Streptococcus pneumoniae meningitis (RR 0.84, 95% CI 0.72 to 0.98).In high-income countries, corticosteroids reduced severe hearing loss (RR 0.51, 95% CI 0.35 to 0.73), any hearing loss (RR 0.58, 95% CI 0.45 to 0.73) and short-term neurological sequelae (RR 0.64, 95% CI 0.48 to 0.85). There was no beneficial effect of corticosteroid therapy in low-income countries.Subgroup analysis for study quality showed no effect of corticosteroids on severe hearing loss in high quality studies.Corticosteroid treatment was associated with an increase in recurrent fever (RR 1.27, 95% CI 1.09 to 1.47), but not with other adverse events. Corticosteroids significantly reduced hearing loss and neurological sequelae, but did not reduce overall mortality. Data support the use of corticosteroids in patients with bacterial meningitis in high-income countries. We found no beneficial effect in low-income countries.